The role of the addressee’s creativity in interpreting allusions - Valotka, Audrius (Lietuvių kalba, 2016)
The article interrogates the conventional conception prevalent in contemporary scientific discourse that the author is the only creator of an allusion, whereas the addressee can only understand the author’s idea / intention “correctly” or “incorrectly”. Based on the new perspective, this study discusses the communicative structure of allusions, investigates the mechanism of interpreting allusions and considers the issue of “arbitration” of meaning-making in interpreting allusions. The key insights offered in the study are as follows: a) Allusion is an open structure which the addressee can interpret in their own way. An adequate / correct understanding of the author’s idea is not a mandatory feature of an allusion. b) The role of the addressee in the process of understanding / interpreting allusions is as crucial as is the role of the creator of the allusion. c) The addressee interprets an allusion rather than trying to guess the author’s idea / intention behind it. d) Understanding of an allusion in a different way than intended by the author does not mean that the process of allusion interpretation is over. e) An allusion which is interpreted differently than intended by the author does not lose its characteristic features. f) The “correctness” of interpreting an allusion may be determined by a person whose background knowledge encompasses both the background knowledge of the author and that of the addressee. On the basis of these theoretical premises, this study continues a previous analysis based on the empirical linguistic data reported in the article Perception of intertexts and identification of the cultural circle in publicistic texts by Rimvydas Valatka (published in the research journal Lietuvių kalba (‘The Lithuanian Language’), Issue 10 (2016)), www.lietuviukalba.lt. Applying the method of respondent testing, the previous study looked at the way contemporary youth perceive unmarked intertexts (primarily allusions) encountered in Lithuanian mass media. The results of the study revealed that Vilnius University students between 18 and 20 years of age are able to recognise and adequately interpret only one fourth of precedent texts alluded to in publicistic texts by Rimvydas Valatka. Respondents showed the highest results in the recognition of cinematographic (49%) and biblical (37%) precedent texts and the lowest results in the identification of historical (12%) precedent texts. The results of the empirical research have demonstrated that precedent texts “migrate” between different areas which correspond to relevant background knowledge of the addressees.